Prevention of Cardiovascular Disease in the Community Through Walking Intervention: Scoping Review - Widyawati Widyawati; Laili Rahayuwati; Citra Windani Mambang Sari; Damar Irza (Jurnal Keperawatan Padjadjaran, 2023)
Background: Cardiovascular disease is the number one killer in the world. The SDGs target reducing mortality through cost-effective prevention efforts. Physical activity, including walking, has been proven to prevent cardiovascular disease. Walking is an activity that is cheap, easy, simple, and does not need tools and skills, so it can be done in general by the community. However, the modern world makes people's walking activities low. There is a need to find evidence of walking interventions that can increase walking and prevent cardiovascular disease. Purpose: This scoping review aims to identify literature focusing on walking interventions that increase footsteps and reduce disease risk to prevent cardiovascular disease. Methods: Following the guidelines for the JBI scoping review methodology. Articles conducted searches on the Ebscho CINAHL, Academic, PubMed, and ProQuest databases from 2013 to 2021. The collected data were extracted in tabular and narrative form. Results: Thirteen articles met the criteria involving 2,910 people from eight countries. Eleven studies used a randomized controlled trial, and two used a quasi-experimental design. Conclusion: Walking interventions that support increased footsteps include: distance, duration per week (< 150 minutes or > 150 minutes), supervision, activities accompanied by socio-cultural activities, counselling, and motivation, in addition to the use of tools such as pedometers, accelerators, and smartwatch is used as a footstep monitor. Intervention in walking is beneficial in reducing cardiovascular diseases risk indicators such as blood pressure, BMI, blood glucose, cholesterol, and triglycerides.